SEJARAH PERKEMBANGAN TIGA LORONG DI KABUPATEN INDRAGIRI HULU - Utari, Sri Rahmi; Isjoni, Isjoni; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Tiga Lorong (Three Hallways) are three areas led by three chiefs entitled Danang Lelo, Jo Mungkuto, Lelo Derajo. Each chief holds their territory of power, they are Danang Lelo Pematang, Jo Mungkuto Baturijal Hulu, Lelo Derajo Baturijal Hilir. These chiefs have a power to govern all the existing costoms in Tiga Lorong. The purpose of this research is to knowing the development of Tiga Lorong in Indragiri Hulu Regency. The method used in this study was a historical reseach method consisting of four stages, namely heuristics (collecting resources), source criticism, interpretation, and historiography. The data collected by doing some interview and summarize book. The data that obtained from interviews and literatur studies are analyzed to their own words. The location of this reseach conducted in Indragiri Hulu especially in Peranap area. This research was conducted at time of issuance of lisence to do this reseach until this thesis fisished. The thecniques of data collection were observation techniques, interview techniques, literature study and documentation techniques. The results showed that during the reign of Indragiri, led by King Hasan who is titled Sultan Salahuddin Syah, the chiefs of Tiga Lorong are just like the subdistrict head, and they led area of Tiga Lorong. Whereas now the chiefs of Tiga Lorong are only responsible for costoms only. And now, Tiga Lorong divided into two-districts, Peranap district and Batang Peranap.Keywords: Tiga Lorong (Three Hallways), Theree chiefs.